The Mechanism of Oxidative Stress in Cells Isolation, Identification, and Genome-Wide Sequence Analysis of Nitrite Amylolytic Bacillus - Jian Jiang (Hindawi Limited, 2022)
To improve the quality of traditional fermented pickles and reduce the nitrite content in the production process of pickles, the target bacteria for efficient nitrite degradation were screened from traditional fermented pickles. Pickles (picked vegetables), a traditional dish favored by many Chinese, are mildly salted and lactic acid-fermented vegetables in China. However, the presence of nitrite in pickles is a bottleneck which limits further development of the pickle industry. More attention is drawn to the problem of the presence of nitrite in pickles. Having harmful effect in the acidic environment produced by gastric acid, nitrite is converted into carcinogenic nitrosamine. After screening several nitrite-degrading bacteria in the early stage, a Gram-positive round ended Bacillus amyloliquefaciens is named as Bacillus amyloliquefaciens JBA-CH9, which can degrade nitrite efficiently. Bacillus amyloliquefaciens is a common bacterium in the food fermentation industry. Then, the optimum conditions for nitrite degradation of the strain were explored according to the inoculation amount, temperature and salinity, and the whole genome of Bacillus amyloliquefaciens JBA-CH9 was sequenced. The results showed that the strain had the best degradation effect on nitrite under the conditions of inoculation amount of 9%, salinity of 5%, and 30°C, and the highest degradation rate of nitrite was 91.47%. The results of whole genome sequencing showed that the strain had a large number of functional genes related to amino acids, carbohydrates, and lipids and contained nitrite reductase genes related to nitrite metabolism. Therefore, Bacillus amyloliquefaciens JBA-CH9 is a functional strain that can degrade nitrite efficiently.